Influence of Dietary Methionine, Folic Acid and Cyanocobalamin and Their Interactions on the Performance of Broiler Breeder - El-Husseiny , O.M.; Soliman, A.Z.M.; Elsherif, H.M.R. (International Journal of Poultry Science, 2018)
Objective: The experiment was conducted to examine the response of the local broiler female line (Cairo B-2), a new strain of the native Egyptian breed White Baladi chicken females which crossed with Arbor Acres grandparent female line males, to certain dietary nutrients including methionine (Meth), folic acid (FA) and vitamin B12. Methodology: The experiment was designed in a 2×2×2 factorial arrangement from 53-64 weeks of age. Seventy two females and twenty four males were randomly assigned to 8 groups of 9 hens and 3 roosters in 3 replicates each. The birds were housed individually and artificially inseminated with pooled semen every 4 weeks. Results: The results indicated that feeding diet containing 0.25% Meth, 13.0 mg kg–1 FA and 0.15 mg kg–1 B12 showed the best egg weight, egg mass, feed conversion ratio, hatchability and 1 day old chick weight followed by the diet containing 0.25% Meth, 13.0 mg kg–1 FA and 0.03 mg kg–1 vitamin B12. Neither egg quality parameters nor blood parameters were significantly affected by either levels of Meth, FA or B12 or their interactions, except for Haugh units and hemoglobin (p